Coping Stress On Mothers Who Works As Health Workers in TTU Districk - Obe, Johan Stefendy; Lerik, Mariana Dinah Ch; Aipipidely, Diana (Universitas Nusa Cendana, 2023)
Mothers who work as health workers have a dual role, namely as a housewife and as a health worker, so they are vulnerable to stress. Working mothers must apply stress coping appropriately so they don't experience stress that can interfere with the mother in carrying out her role. This study aims to provide an overview of coping with stress on mothers who work as health workers in TTU District. There were 250 participants who were taken using a purposive sampling. The method used in this research is descriptive quantitative. The results showed that the participants in the research were able to cope with stress well. The results of this study also show coping strategies in the form of increasing family finances, increasing self-ability, changing the way to handle problems